The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.3171/jns/2008/108/3/0437
|View full text |Cite
|
Sign up to set email alerts
|

Could late rebleeding overturn the superiority of cranial aneurysm coil embolization over clip ligation seen in the International Subarachnoid Aneurysm Trial?

Abstract: Object. The present purpose is to define the sensitivity of the superiority of coil embolization observed in the International Subarachnoid Aneurysm Trial (ISAT) according to the rate of late rebleeding over a reasonable range, and to find the range of rebleeding rates for which it may be overturned. In the ISAT, coil embolization appears to be safer than clip ligation at 1 year, and clip occlusion has better long-term efficacy at preventing rebleeding. This leaves open the question of which is better in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(63 citation statements)
references
References 31 publications
2
59
0
1
Order By: Relevance
“…However, while coiling has become the procedure of choice for most patients, clipping is still being offered to a substantial number of patients, especially those who are younger. The lower use of coiling in younger patients is supported by the ISAT results, which showed little difference in outcomes for clipping and coiling for patients 40 years old and younger, 22 and by the better durability of surgical clipping.…”
Section: Discussionsupporting
confidence: 63%
“…However, while coiling has become the procedure of choice for most patients, clipping is still being offered to a substantial number of patients, especially those who are younger. The lower use of coiling in younger patients is supported by the ISAT results, which showed little difference in outcomes for clipping and coiling for patients 40 years old and younger, 22 and by the better durability of surgical clipping.…”
Section: Discussionsupporting
confidence: 63%
“…1 Furthermore, follow-up data from the ISAT study suggest that younger patients may have better long- term outcomes when treated with clipping compared with coiling. 16 The entry criteria for ISAT and BRAT differed markedly. Only 22% of eligible patients were entered into ISAT.…”
Section: To Clip or To Coil: Is That The Question?mentioning
confidence: 99%
“…This final report demonstrated the increased risk of rebleeding from a coiled aneurysm compared with a clipped aneurysm although the number of recurrent bleeding episodes was very small in both treatment groups. At the conclusion of the ISAT, coil embolisation appeared to be more advantageous than clip ligation regarding death and severe disability at one year, and clip occlusion had better long-term efficacy in order to prevent recurrent bleeding and to result a better long-term outcome especially in patients younger than 40 years of age (19). Recently, The Barrow Ruptured Aneurysm Trial (BRAT) reported the initial results (18).…”
Section: Goksu E Et Al: Follow-up Screening Of Intracranial Aneurysmsmentioning
confidence: 97%